2020
DOI: 10.3389/fpsyt.2020.00295
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol at Certain Doses Alleviates Aggressive and Anxiety-Like Behaviours in Two Premenstrual Dysphoric Disorder Rat Models

Abstract: Premenstrual dysphoric disorder (PMDD) is a severe form of premenstrual syndrome (PMS), a common mental health disturbance associated with several periodic psychological symptoms in women. Selective serotonin reuptake inhibitors (SSRIs) are the first-line treatment for PMS/PMDD patients; however, side effects are inevitable, especially in long-term treatment. In previous studies, the natural compound paeonol in Moutan Cortex was found to play effective roles in central nervous system disorders with its anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 48 publications
1
10
0
1
Order By: Relevance
“…To our delight, thymol, paeonol and eugenol were tolerated, producing the resulting esters in medium yields (3da, 3db, and 3dc). 13–15 We were pleased to find that the direct esterification of cholesterol (3dd), 16 a cyclopentane polyhydrophenanthrene derivative necessary for the human body; and oleanolic acid (3de), 17 a medicine for treating infectious acute jaundice hepatitis, furnished the esterification products in low to medium yields, demonstrating the synthetic advantage of the I 2 /KH 2 PO 2 protocol ( Table 4 ). However, the KI/P(OEt) 3 protocol, delivered the esterification products only in trace amounts.…”
Section: Resultsmentioning
confidence: 99%
“…To our delight, thymol, paeonol and eugenol were tolerated, producing the resulting esters in medium yields (3da, 3db, and 3dc). 13–15 We were pleased to find that the direct esterification of cholesterol (3dd), 16 a cyclopentane polyhydrophenanthrene derivative necessary for the human body; and oleanolic acid (3de), 17 a medicine for treating infectious acute jaundice hepatitis, furnished the esterification products in low to medium yields, demonstrating the synthetic advantage of the I 2 /KH 2 PO 2 protocol ( Table 4 ). However, the KI/P(OEt) 3 protocol, delivered the esterification products only in trace amounts.…”
Section: Resultsmentioning
confidence: 99%
“…In general, our results showed that paeonol repressed migration and invasion of ecESCs through attenuation of hypoxia-triggered autophagy, and ameliorated histopathological changes and inflammatory response of endometriotic rats in a HIF-1α dependent manner, suggesting that paeonol might serve as a novel therapeutic strategy for the treatment of endometriosis. Moreover, according previous study [33], paeonol might be intraperitoneally introduced into the patients with endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…The test started with the placement of the rats at the centre of the light chamber and lasted for 5 min. The XR-Super Maze tracking system was used to record the behaviour and analyse the total distance, light area distance, time in the light area, and light area entries [ 32 ].…”
Section: Methodsmentioning
confidence: 99%